Impact of viscosity variations in dual-polymer artificial tears on corneal regularity and aberration - Halmi, Husna Alia; Hilmi, Mohd Radzi; Md Rejab, Noor Shazana; Wolffsohn, James Stuart (IIUM Press, 2024)
Background: This study was done to explore the possibility of the usage of different viscosities in artificial tears (Systane Ultra and Hydration) in detecting changes in corneal aberration on dry eye patients. Methods: 103 diagnosed dry eyes were observed in this study and two different artificial tears with different viscosities were instilled randomly in each eye. Corneal aberration measurement with Fourier index (Spherical aberration (SA), trefoil and coma) was then captured for 10 minutes using CASIA with a 1-minute time interval. Normal saline was instilled before the treatment was given (referred to as baseline). Repeated measure analysis of variance (RM ANOVA) and paired sample t-test were used to evaluate the effects of artificial tears after instillation and comparison between each specific time interval respectively. The P-value of 0.05 was set as the level of significance. Results: Corneal aberration with artificial tears was then compared to normal saline and the results showed that there was no significant difference between artificial tears in terms of retention time after 10 minutes (p>0.05) in dry eye participants. Both groups demonstrated significant improvements from baseline and there was a significant difference from baseline (p<0.05). Conclusion: Instillation of high viscous artificial tear produce better uniformity of the corneal surface resulting in lower corneal aberration.